(untitled) (Global Journal of Human-Social Science, 2014)
Military Aviation is an inherently stressful occupation and it demands a high level of physical endurance and mental stamina. The personnel selection for safety-sensitive jobs such as air traffic controllers is a crucial task. Choosing the wrong person for this job can have visibly disastrous results. The objective of this study is to develop and validate a non-cognitive test for selection of the air traffic controllers. A Personality Based Job Analysis was conducted on 87 Air Traffic Controllers, representing different seniority and ranks which revealed high ratings for Adjustment, Prudence, Ambition, leadership and openness to experience. On the basis of job analysis 200 non cognitive items were developed. The initial 200 items were subjected to 10 Subject Matter Experts (SME) which resulted in 100 items and was administered to 902 military aspirant candidates. Item Analysis and Factor Analysis resulted in the 20 items with four extracted factors namely Social Potency, Prudence, Sensitivity and Extraversion. The final non-cognitive test displayed good internal consistency and validity. Convergent and discriminant validity of the measure was established through comparison with other personality measures. The psychometric property of the non-cognitive test indicates that it is a reliable and valid measure to be used for an evaluation of Job specific personality for the selection of Air Traffic Controllers.